Polymorphisms in MTHFR, MS and CBS genes and homocysteine levels in a Pakistani population. - Mohsin Yakub (Public Library of Science (PLoS), 2012)
Background Hyperhomocysteinemia (>15 µmol/L) is highly prevalent in South Asian populations including Pakistan. In order to investigate the genetic determinants of this condition, we studied 6 polymorphisms in genes of 3 enzymes--methylenetetrahydrofolate reductase (MTHFR; C677T; A1298C), methionine synthase (MS; A2756G), cystathionine-β-synthase (CBS; T833C/844ins68, G919A) involved in homocysteine metabolism and investigated their interactions with nutritional and environmental factors in a Pakistani population. Methodology/principal findings In a cross-sectional survey, 872 healthy adults (355 males and 517 females; age 18-60 years) were recruited from a low-income urban population in Karachi. Fasting venous blood was obtained and assessed for plasma/serum homocysteine; folate, vitamin B12, pyridoxal phosphate and blood lead. DNA was isolated and genotyping was performed by PCR-RFLP (restriction-fragment-length-polymorphism) based assays. The average changes in homocysteine levels for MTHFR 677CT and TT genotypes were positive [β(SE β), 2.01(0.63) and 16.19(1.8) µmol/L, respectively]. Contrary to MTHFR C677T polymorphism, the average changes in plasma homocysteine levels for MS 2756AG and GG variants were negative [β(SE β), -0.56(0.58) and -0.83(0.99) µmol/L, respectively]. The average change occurring for CBS 844ins68 heterozygous genotype (ancestral/insertion) was -1.88(0.81) µmol/L. The combined effect of MTHFR C677T, MS A2756G and CBS 844ins68 genotypes for plasma homocysteine levels was additive (p value <0.001). Odds of having hyperhomocysteinemia with MTHFR 677TT genotype was 10-fold compared to MTHFR 677CC genotype [OR (95%CI); 10.17(3.6-28.67)]. Protective effect towards hyperhomocysteinemia was observed with heterozygous (ancestral/insertion) genotype of CBS 844ins68 compared to homozygous ancestral type [OR (95% CI); 0.58 (0.34-0.99)]. Individuals with MTHFR 677CT or TT genotypes were at a greater risk of hyperhomocysteinemia in folate and vitamin B12 deficiencies and high blood lead (p value <0.05) level. Conclusions Gene polymorphism (especially MTHFR C677T transition), folate and vitamin B12 deficiencies, male gender and high blood lead level appear to be contributing towards the development of hyperhomocysteinemia in a Pakistani population.